Comparison of Calcium and Barium Microcapsules as Scaffolds in the Development of Artificial Dermal Papillae - Liu, Yang (Biomed Res Int, 2016)
This study aimed to develop and evaluate barium and calcium microcapsules as candidates for scaffolding in artificial dermal papilla. Dermal papilla cells (DPCs) were isolated and cultured by one-step collagenase treatment. The DPC-Ba and DPC-Ca microcapsules were prepared by using a specially designed, high-voltage, electric-field droplet generator. Selected microcapsules were assessed for long-term inductive properties with xenotransplantation into Sprague-Dawley rat ears. Both barium and calcium microcapsules maintained xenogenic dermal papilla cells in an immunoisolated environment and induced the formation of hair follicle structures. Calcium microcapsules showed better biocompatibility, permeability, and cell viability in comparison with barium microcapsules. Before 18 weeks, calcium microcapsules gathered together, with no substantial immune response. After 32 weeks, some microcapsules were near inflammatory cells and wrapped with fiber. A few large hair follicles were found. Control samples showed no marked changes at the implantation site. Barium microcapsules were superior to calcium microcapsules in structural and mechanical stability. The cells encapsulated in hydrogel barium microcapsules exhibited higher short-term viability. This study established a model to culture DPCs in 3D culture conditions. Barium microcapsules may be useful in short-term transplantation study. Calcium microcapsules may provide an effective scaffold for the development of artificial dermal papilla.